2015
DOI: 10.1111/caim.12142
|View full text |Cite
|
Sign up to set email alerts
|

Industrial Designers: Are You Ready for Foreign Markets? Assessing Designer Confidence and Prediction Accuracy in a Transnational Marketing Context

Abstract: In order to boost sales in foreign markets and compete with emerging local competitors, global companies from developed countries are realizing that they need to develop products specifically for the local markets. Meanwhile, companies in developing nations are building up their design staff and seeking to establish their own global brands. This recent growth in design activity targeting overseas markets suggests the need for academic research to better understand the phenomenon of design expertise transfer ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
(143 reference statements)
1
7
0
Order By: Relevance
“…Contrasting further, designers identify themselves as somewhere between these two extremes, neither prioritising creativity or responsibility nor early or midphase NPD (Figure 3), but rather highlighting elements such as Confidence and Empathy across the whole NPD process. These detailed insights extend prior comparisons of education and practice, which have typically described overall development of expertise (Smith 2015) and competency (Helfat and Martin 2015), or focused on specific DPI elements in isolation, such as confidence (Zhang 2015) the professional environment to balance social-perception of role-models (Ibarra 1999).…”
Section: Contrasting Social-perceptions and Self-perception Of Designsupporting
confidence: 58%
“…Contrasting further, designers identify themselves as somewhere between these two extremes, neither prioritising creativity or responsibility nor early or midphase NPD (Figure 3), but rather highlighting elements such as Confidence and Empathy across the whole NPD process. These detailed insights extend prior comparisons of education and practice, which have typically described overall development of expertise (Smith 2015) and competency (Helfat and Martin 2015), or focused on specific DPI elements in isolation, such as confidence (Zhang 2015) the professional environment to balance social-perception of role-models (Ibarra 1999).…”
Section: Contrasting Social-perceptions and Self-perception Of Designsupporting
confidence: 58%
“…Third, this research enriches literature on design expertise, which is an under‐researched area in the NPD and design literature (Cross, ; Lawson and Dorst, ; Zhang, ). While the literature on design expertise mostly embraces the concepts of novice and expert (Ozkan and Dogan, ), with level of expertise often measured by years of experience (Ericsson and Smith, ), this study shows that considering the level of expertise is not sufficient in the marketing–external design relationship.…”
Section: Resultsmentioning
confidence: 80%
“…Experts are individuals who are perceived to be comparatively outstanding in a particular domain because they possess greater knowledge, skills, and experience than nonexperts (Ericsson and Smith, 1991). This leads to the distinction between novices and masters (Cross, 2004;Lawson and Dorst, 2013;Zhang, 2015). While novices focus on product functionality and favor mental leaps, expert designers value product symbols, and analogy making (Chai, Cen, Ruan, Yang, and Li, 2015).…”
Section: Specificities Of External Design Management: Innovativenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Confidence levels can be determined by several methods. For example, in a study on assessing confidence and prediction accuracy of designers from different cultures and experience levels, Zhang (2015) presents a method of determining confidence levels using a Likert scale (e.g., 1 = 'not at all confident' and 7 = 'very confident') (Likert 1932). Interestingly, Zhang found that both experienced and novice designers are more confident when designing for their home market than for a foreign market.…”
Section: Step 2: Determine the Value Functions Constraints And Confmentioning
confidence: 99%